River system analysis and management - Sharma, Nayan (Springer, 2016)
The main thrust of this book is focused on addressing the various interrelated processes, analysis and activities bearing upon sound river management. River basins are complex systems. They are open systems with sometimes ill-defined boundaries. It refers to various aspects essential to achieve a sustainable development of river basins, including water demand and river management, intensified erosion, land water degradation and stream flow pollution which call for appropriate river restoration and training measures. A viable theory for river management must reconcile the various processes that occur at different scales in order to develop a knowledge base by synthesizing research and field studies results. The book is intended to augment the knowledge base of behaviour of rivers and analyse the issues related to rivers so as to develop river system management techniques emerging from in-depth scientific analysis as a priority. This book pools together the expertise, the in-depth knowledge and the experience of the people representing different disciplines bearing on the related aspects of analysis and management of river systems. Audience The book is expected to be useful to academics, practitioners, scientists, water managers, environmentalists, administrators, researchers and students who are involved and have stakes in water management and river system analysis.
6: River Basin Impact Assessment of Changing Land Use and Climate by Applying the ILWRM Approach in Africa and Asia.
Keywords: Integrated water development.; Stream ecology.; Stream conservation.; elektronické knihy; electronic books